2019
DOI: 10.7759/cureus.4182
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitude Towards Cardiopulmonary Resuscitation Among Doctors of a Tertiary Care Hospital in Karachi

Abstract: Objective Cardiac arrest is an emergency, which can be managed effectively by sound knowledge and practice of basic life support (BLS) skills. However, it has been globally reported that the knowledge of doctors regarding cardiopulmonary resuscitation (CPR) and BLS is sub-standard. We conducted this study with the aim to assess the knowledge and attitude of doctors toward CPR in Dr. Ruth K.M. Pfau Civil Hospital, one of the largest tertiary care hospitals, in Pakistan. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 22 publications
0
9
0
2
Order By: Relevance
“…Even though, bystander CPR has gained widespread recognition as a lifesaving skill; implementation of bystander CPR training and public access to it is generally limited in LMICs. However, in Pakistan, healthcare professionals have inadequate knowledge of CPR (49,50). There are several major concerns that bystanders may have regarding their readiness to perform CPR in Pakistan, including making a mistake when performing CPR or unintentionally injuring the patient, being concerned about legal consequences, and hesitating to perform CPR on the opposite gender which is consistent with the previous ndings (51).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though, bystander CPR has gained widespread recognition as a lifesaving skill; implementation of bystander CPR training and public access to it is generally limited in LMICs. However, in Pakistan, healthcare professionals have inadequate knowledge of CPR (49,50). There are several major concerns that bystanders may have regarding their readiness to perform CPR in Pakistan, including making a mistake when performing CPR or unintentionally injuring the patient, being concerned about legal consequences, and hesitating to perform CPR on the opposite gender which is consistent with the previous ndings (51).…”
Section: Discussionmentioning
confidence: 99%
“…Within Pakistan, studies have focused mostly on healthcare professionals, not on the need to train members of the general population in performing by-standing CPR. (19,23) . Encouragingly, a few studies have shown that members of the general population may be receptive to receiving such training.…”
mentioning
confidence: 99%
“…It lacks a system for ACP, and most physicians are unaware of practices to honor patients' dignity near the end of their lives. 15,41 Moreover, EoL discussion in a relatively young patient requires expertise, which is not routinely taught in Pakistani medical schools. 42 Our study has several strengths and limitations.…”
Section: Discussionmentioning
confidence: 99%
“… 12 , 14 In addition, Pakistani physicians lack training in end-of-life (EoL) care and have a predilection toward performing cardiopulmonary resuscitation regardless of prognosis or patient wishes. 15 Therefore, studies exploring EoL care gaps and solutions in the country are critically needed.…”
Section: Introductionmentioning
confidence: 99%
“…Despite global organizations for CPR stressing the importance of the quality of CPR skills and training [16], the latter remain low [15,[25][26][27][28][29][30][31]. Despite the acknowledged benefit of CPR skills in health professionals and the general public [15][16][17][18]24], no previous study has investigated the knowledge of CPR among physiotherapists.…”
Section: Discussionmentioning
confidence: 99%